Analisis Tingkat Literasi Keuangan SMK N 1 Singaraja dan SMA N 4 Singaraja - El Dimas Handy Irhamy; Wayan Cipta (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study aims to determine the comparison of the level of financial literacy of SMK N 1 Singaraja and SMA N 4 Singaraja. This research is a type of quantitative research with a comparative descriptive approach. The subjects in this study were students of SMK N 1 Singaraja and SMA N 4 singaraja and the object in this study was the level of student financial literacy. The sample in this study were 97 by using Slovin formula. The data used are primary data using a questionnaire. The questionnaire consisted of two parts, namely personal data and questions related to financial literacy. The questionnaire was analyzed with comparative descriptive analysis techniques. The average overall financial literacy rate is 71.15% in the medium category. The level of financial literacy of SMK N 1 Singaraja is 72.8% included in the medium category and SMA N 4 Singaraja by 69% is included in the medium category. The difference in the level of financial literacy is not too significant because the level of literacy does not differ too much and still in the same category.